Qualidade das uvas Niágara Rosada e Isabel em diferentes ambientes no Espírito Santo - Meneghelli, Caroline Merlo (2018)
The vine is a culture of great national and world expression and many factors can interfere in the wine production as well as the altitude of cultivation. The objective of this study was to evaluate the quality of the varieties (Vitis labrusca L.) Niagara